Application of Project Based Learning with Picture and Picture Technique on Creative Writing Skills of Elfchen & Haikus Poetry of Class XI 1 Students of SMAN 7 Malang - Indrisani, Yovika; Ardiyani, Dewi Kartika (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This study is to describe the application of Project Based Learning (PjBL) learning model with Picture and Picture (PnP) technique on creative writing skills of German Elfchen and Haikus Poetry in class XI 1 SMAN 7 Malang. This descriptive qualitative research involved 36 students of class XI 1 SMAN 7 Malang, using observation sheets and questionnaires as instruments. The observation results showed that students could follow the learning process according to the steps of the PjBL learning model with a combination of PnP techniques. Students gave positive responses to the PjBL learning model and PnP technique. The combination of PnP and PjBL techniques makes it easier for students to solve problems in developing creative ideas that are poured into the form of Elfchen & Haikus poetry writing. Overall, the application of the PjBL learning model combined with the PnP technique can develop students' creativity and train their skills in writing literary works in the form of Elfchen & Haikus poetry.